Evaluation the Effect of Micro-osteoperforation on the Tooth Movement Rate and the Level of Pain on Miniscrew-supported Maxillary Molar Distalization: A Systematic Review and Meta-analysis - Nadia Sotelo Núñez; Zahra Hatamzade; Seyede Sana Zamiri; Mehrnaz Safi (International Journal of Scientific Research in Dental and Medical Sciences, 2020)
Background and aim: The recent meta-analysis and systematic review concentrated on the retraction of canine teeth. There was no previous meta-analysis or systematic review to evaluate the effects of micro-osteoperforations on the maxillary molar distalization. The present meta-analysis and systematic review were intended to assess the effect of micro-osteoperforatio on the tooth movement rate and the level of pain on the miniscrew-supported maxillary molar distalization. Materials and methods: From the electronic databases, PubMed, Cochrane Library, Embase, ISI have been used to perform systematic literature until July 2020. Therefore, a software program (Endnote X8) has been utilized for managing electronic titles. Searches were performed with mesh terms. The Cochrane Collaboration tool was deployed to assess the quality of the randomized clinical trials that were included. We also used SYRCLE's (SYRCLE’s RoB tool is an adapted version of the Cochrane RoB tool.) risk of tool bias for animal interventional studies was included. Mean differences between the two groups (MOP and without MOP) with a 95% confidence interval (CI), fixed-effect model, and Inverse-variance method were calculated. Results: Totally, 65 potentially relevant studies were found in the electronic search according to their titles and abstracts. Lastly, merely three publications were eligible according to the inclusion criteria of the current systematic review. In humans, the mean difference of tooth movement was (MD, 0.00mm 95% CI -0.00, and 0.00. P= 0.58) among one study. Conclusion: Animal studies showed positive effects and statistically significant of micro-osteoperforation interventions on tooth movement.